Clinical, Genetic, and Protein Structural Aspects of Familial Dysalbuminemic Hyperthyroxinemia and Hypertriiodothyroninemia - Kragh-Hansen, Ulrich; Galliano, Monica; Minchiotti, Lorenzo (Frontiers in Endocrinology, 2017)
Familial dysalbuminemic hyperthyroxinemia (FDH-T4) and hypertriiodothyroninemia (FDH-T3) are dominantly inherited syndromes characterized by a high concentration of thyroid hormone in the blood stream. The syndromes do not cause disease, because the concentration of free hormone is normal, but affected individuals are at risk of erroneous treatment. FDH-T4 is the most common cause of euthyroid hyperthyroxinemia in Caucasian populations in which its prevalence is about 1 in 10,000 individuals, but the prevalence can be much higher in some ethnic groups. The condition is caused by a genetic variant of human serum albumin (HSA); Arg218 is mutated to histidine, proline or serine or Arg222 is changed to isoleucine. The disorder is characterized by greater elevation in serum L-thyroxine (T4) than in serum triiodothyronine (T3); T4 can be increased by a factor 8 ‒ 15. The high serum concentration of T4 is due to modification of a binding site located in the N-terminal half of HSA (in subdomain IIA). Thus, mutating Arg218 or Arg222 for a smaller amino acid reduces the steric restrictions in the site and creates a high-affinity binding site. The mutations can also affect binding of other ligands and can perhaps cause modified pharmacokinetics of albumin-binding drugs. In normal HSA, the high-affinity site has another location (in subdomain IIIB). Different locations of these sites imply that persons with and without FDH-T4 can have different types of interactions, and thereby complications, when given albumin-binding drugs. FDH-T3 is caused by a leucine to proline mutation in position 66 of HSA, which results in a large increment of the binding affinity for T3 but not for T4. For avoiding unwanted treatment of euthyroid persons with hyperthyroxinemia or hypertriiodothyroninemia, protein sequencing and/or sequencing of the albumin gene should be performed.